Determination of Mn site in BaTiO3 by X-ray absorption spectroscopy - Yimnirun R. (2014)
In this work, an experimental X-ray Absorption Spectroscopy (XAS) measurement was employed to determine the local structure of Mn in BaTiO 3. Synchrotron X-ray absorption near-edge structure (XANES) experiments were performed on Mn-doped BaTiO3 samples. The BaTi 0.8Mn0.2O3 powders were used for the XAS experiment. XAS spectra at the Mn K-edge were recorded in transmission mode. The spectra were collected at ambient temperature with a Ge(111) double crystal monochromator and recorded after performing an energy calibration. The features of the measured Mn K-edge XANES were consistent with Mn on the Ti site and inconsistent with Mn on other sites. The clear agreement was the strongest evidence of Mn substituting for Ti in BaTiO3. © 2008 Trans Tech Publications, Switzerland.